2014
DOI: 10.1590/s0100-736x2014001000018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insulin-like Growth Factor I (IGF-I) on the survival and the in vitro development of caprine preantral follicles

Abstract: RESUMO.-[Influência do Fator de Crescimento Semelhante à Insulina-I (IGF-I) sobre a sobrevivência e o desenvolvimento in vitro de folículos pré-antrais capri-nos.] O objetivo do presente estudo foi investigar os efeitos do fator de crescimento semelhante a insulina-I (IGF-I) na sobrevivência, ativação (transição de folículos primordiais para primários) e crescimento de folículos pré-antrais caprinos cultivados in vitro. Fragmentos de córtex ovariano foram cultivados por um e sete dias na ausência ou presença d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…Fortune et al () reported that the addition of IGF‐1 to the culture medium increased the atresia of preantral follicles in bovines after the in vitro culture. Costa et al () concluded that the addition of IGF‐1 in the culture medium activated the development of caprine preantral follicles. Nevertheless, that is not enough to keep the rate of follicular survival after 7 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“…Fortune et al () reported that the addition of IGF‐1 to the culture medium increased the atresia of preantral follicles in bovines after the in vitro culture. Costa et al () concluded that the addition of IGF‐1 in the culture medium activated the development of caprine preantral follicles. Nevertheless, that is not enough to keep the rate of follicular survival after 7 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“…A proteína albumina sérica bovina (BSA) é muito utilizada no meio de CIV por favorecer o desenvolvimento folicular e a produção de oócitos meioticamente competentes (Rodrigues et al, 2010), bem como manter a estrutura tridimensional folicular (Itoh, Kacchi, Abe, Sendai, & Hoshi, 2002). Há ainda outras substâncias, como hormônios: insulina, FSH, hormônio do crescimento (GH) e tiroxina (Ferreira et al, 2016;Cadenas et al, 2017;Ferreira et al, 2020;Paes et al, 2020), fatores de crescimento: fator semelhante à insulina tipo 1 (IGF-1), fator de crescimento epidérmico (EGF), fator fibroblástico básico (FGF-2) e fator endotelial vascular (VEGF; Costa et al, 2014;Santos et al, 2014a;Santos et al, 2014b;Cadenas et al, 2017), MC produzido a partir de CTMs (Bezerra et al, 2019) e antioxidantes, como anetol (Sá et al, 2020) que também ao serem adicionados ao meio estimulam e favorecem o desenvolvimento dos folículos cultivados in vitro.…”
Section: Meios E Suplementosunclassified
“…Relevant for the present review, the addition of IGF-1 to the medium of ovarian tissue culture has been reported to promote PMF activation in caprine and ovine ( Martins et al 2010 , Luz 2013 , Costa 2014 ) and human follicles ( Louhio et al 2000 ). Moreover, Bezerra et al (2018) , reported that IGF-1 promoted activation of ovine PMFs in vitro , stimulating at the same time granulosa cell proliferation and reducing DNA fragmentation in such cells through the PI3K/Akt pathway.…”
Section: Pi3k/akt/mtorc1 Pathwaysmentioning
confidence: 99%